A Fluid Pulse on the Hikurangi Subduction Margin: Evidence From a Heat Flux Transect Across the Upper Limit of Gas Hydrate Stability. Issue 24 (29th December 2017) - Pecher, I. A.; Villinger, H.; Kaul, N.; Crutchley, G. J.; Mountjoy, J. J.; Huhn, K.; Kukowski, N.; Henrys, S. A.; Rose, P. S.; Coffin, R. B.
Abstract: A transect of seafloor heat probe measurements on the Hikurangi Margin shows a significant increase of thermal gradients upslope of the updip limit of gas hydrate stability at the seafloor. We interpret these anomalously high thermal gradients as evidence for a fluid pulse leading to advective heat flux, while endothermic cooling from gas hydrate dissociation depresses temperatures in the hydrate stability field. Previous studies predict a seamount on the subducting Pacific Plate to cause significant overpressure beneath our study area, which may be the source of the fluid pulse. Double‐bottom simulating reflections are present in our study area and likely caused by uplift based on gas hydrate phase boundary considerations, although we cannot exclude a thermogenic origin. We suggest that uplift may be associated with the leading edge of the subducting seamount. Our results provide further evidence for the transient nature of fluid expulsion in subduction zones. Key Points: Transient fluid expulsion causes elevated thermal gradients on the seafloor landward of the pinch out of the base of gas hydrate stability Temperatures within the gas hydrate stability field are depressed by endothermic cooling from gas hydrate dissociation Double‐BSRs in the study area are likely to be caused by uplift from subduction of a seamount, which also causes fluid expulsion